2019
DOI: 10.5194/acp-19-5959-2019
|View full text |Cite
|
Sign up to set email alerts
|

Timescales of secondary organic aerosols to reach equilibrium at various temperatures and relative humidities

Abstract: Secondary organic aerosols (SOA) account for a substantial fraction of air particulate matter, and SOA formation is often modeled assuming rapid establishment of gas-particle equilibrium. Here, we estimate the characteristic timescale for SOA to achieve gas-particle equilibrium under a wide range of temperatures and relative humidities using a state-of-the-art kinetic flux model. Equilibration timescales were calculated by varying particle phase state, size, mass loadings, and volatility of organic compounds i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 74 publications
(92 reference statements)
2
69
0
Order By: Relevance
“…Although the Shiraiwa and Seinfeld [272] and Li and Shiraiwa [311] model results indicate equilibrium mass transfer even for semi-solid SOA in the case of SVOC, the picture is incomplete. Zhou et al [312] find that the heterogeneous reaction of benzoapyrene (BaP) with ozone in SOA coated ammonium sulfate particles is significantly affected by the viscosity of the SOA shell, which depends on RH.…”
Section: Organic Aerosol Mass Transfer Summarymentioning
confidence: 96%
See 2 more Smart Citations
“…Although the Shiraiwa and Seinfeld [272] and Li and Shiraiwa [311] model results indicate equilibrium mass transfer even for semi-solid SOA in the case of SVOC, the picture is incomplete. Zhou et al [312] find that the heterogeneous reaction of benzoapyrene (BaP) with ozone in SOA coated ammonium sulfate particles is significantly affected by the viscosity of the SOA shell, which depends on RH.…”
Section: Organic Aerosol Mass Transfer Summarymentioning
confidence: 96%
“…Li and Shiraiwa [311] evaluate the gas-particle mass equilibrium timescales for SOA under a large range of temperature and RH conditions found in the troposphere using the KM-GAP model. They find that for semi-volatile compounds the equilibrium timescale is on the order of seconds or minutes under conditions found in the planetary boundary layer (PBL), excluding low temperature environments.…”
Section: Organic Aerosol Mass Transfer Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, gas-phase oxidation is described kinetically, while gas-particle partitioning is often approximated by quasi-instantaneous equilibrium partitioning of the oxidation products (Pankow, 1994;Shrivastava et al, 2017a;Tsigaridis et al, 2014). The assumption of quasi-instantaneous gas-particle equilibration, however, is in question if particles are highly viscous, semi-solid or glassy -especially at low temperatures and low relative humidity (RH) (Li and Shiraiwa, 2019;Shiraiwa and Seinfeld, 2012). Experimental studies found kinetic limitations for gas uptake and particle evaporation at low RH (Liu et al, 2016;Perraud et al, 2012;Vaden et al, 2011;Yli-Juuti et al, 2017), but not for mixing in SOA at medium or high RH (Ye et al, 2016;Ye et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…By solving analytical transport equations, the equilibration timescales of partitioning for volatile inorganic compounds were found to depend on the size of particles (Meng and Seinfeld, 1996). More recently, there have been numerical simulations for secondary organic aerosol (SOA) as a function of temperature and relative humidity (Shiraiwa and Seinfeld, 2012;Li and Shiraiwa, 2019). Alternatively, equilibration timescales may also be obtained experimentally.…”
Section: Introductionmentioning
confidence: 99%